The effects of ultrasonic scaling duration and replication on caspase-3 expression of Sprague Dawley rat's pulp cells - Archadian Nuryanti; Marsetyawan HNE Soesatyo; Dewi Agustina; Siti Sunarintyas (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Ultrasonic scaling has been used commonly for stain and calculus removal in dental clinic for over 60years. Previous researches even had proved that ultrasonic scaling may give effects on the surface of tooth root. Ultrasonic wave exposure for 20 seconds or more can increase caspase-3 activity as an indicator of increased apoptotic cells associated with tissue damage. Purpose: This research was aimed to investigate the effects of ultrasonic scaling duration and replication on caspace-3 expression in dental pulp cells. Methods: The samples of this research were 54 male Sprague Dawley rats aged 2 months old divided into 2 groups, each of which consisted of 27 mice. The first group was induced with stain, while the second group was not. Each group was divided into 3 subgroups for ultrasonic scaling 1, 3, and 5 times. Each subgroup was divided into 3 sub-subgroups for duration procedure of 15, 30 and 60 seconds respectively. During scaling process, those rats were anesthetized using 0.1 ml of ketamine and 0.1 ml of xylol added to 2 ml of distilled water injected intramuscularly into their right thigh as much as 0.4 ml. Scaling was done on buccal surface of right first maxillary molar from cervical to occlusal. The teeth were decalcified and embedded in paraffin, then their sagittal plane was cut for thickness of 3µm and painted with immunohystochemistry for detecting caspace-3 expression of cell within dental pulp. Results: The results showed that the duration and replication of ultrasonic scaling procedures affected on the expression of caspace-3 cells as analyzed with Univariate Analisis of Variance test (p<0.05). Conclusion: It can be concluded that duration and replication of ultrasonic scaling procedure on teeth with and without stain enhauced the expression of caspace-3 in dental pulp cells.